Meningkatkan Keterampilan Bahasa Arab Melalui Media Video - Siti Fatimah; Lili Musyafa'ah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
Video-based learning media has become an effective tool in teaching Arabic, offering an innovative and exciting way to support the learning process. This article explores the use of video media as an Arabic learning tool, identifying benefits, challenges, and implications. The study uses qualitative methods with case studies analysis and in-depth interviews with teachers and students, as well as quantitative methodology through surveys to measure the effectiveness of video media in improving language skills. The results show that video media enriches learning experiences by providing authentic and interactive material, improving listening and speaking skills, and motivating students. However, challenges such as limited access to technology and the need for quality video material were also identified. This article suggests improving the quality of educational video, providing wider access, and training for teachers to maximize the potential of video media in learning Arabic. This research provides valuable insights for educators and curriculum developers in using video media to improve Arabic learning outcomes.